A molecular-genetic study of the human Y-chromosome - Oosthuizen, C. J. Joubert(Christiaan Johannes Joubert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1988.